The effect of n‐acetyl‐cysteine on recovery of the facial nerve after crush injury. Issue 3 (10th April 2017) - Rivera, Andrew; Raymond, Mallory; Grobman, Ariel; Abouyared, Marianne; Angeli, Simon I.
Abstract : Objective: Facial nerve dysfunction can vary in severity and recovery is dependent on the character of the injury. N‐acetyl‐cysteine prevents oxidative stress and cellular damage, and its use in the setting of nerve dysfunction from crush injury has not yet been established. In this study, rats with facial nerve crush injury will be treated with n‐acetyl‐cysteine or control and functional recovery and electrophysiologic outcome will be compared. Study Design: Prospective, randomized animal study Methods: Twenty‐four Wistar rats underwent unilateral facial nerve crush injury. Rats were implanted with a subcutaneous osmotic pump filled with saline (n = 12) or n‐acetyl‐cysteine 50 mg/kg/day (n = 12). Functional and electromyographic recovery was recorded at two and four weeks postoperatively. Results: When compared to untreated rats, n‐acetyl‐cysteine treated rats had a greater electromyography amplitude recovery at 2 weeks with regard to eye blink (p=0.006) but not vibrissae function. At four weeks, the electromyography amplitude recovery of the vibrissae function was greater in n‐acetyl‐cysteine treated rats (P=0.001), but the amplitude recovery difference in eye blink was only marginally significant between groups (p=0.07). The functional score was higher in n‐acetyl‐cysteine‐treated rats than in untreated rats at all of the time points. Conclusion: This study demonstrated that n‐acetyl‐cysteine facilitated facial nerve recovery with improved functional and electromyography outcomes in the setting of crush injury. Level of Evidence: NA